Kidney Bean Yoghurt is Effective to Improve Immune System and Sleep Quality Among Elderly in Yogyakarta - Putriningtyas, Natalia Desy; Astuti, Ari Tri (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
This study aimed to assess the effect of kidney bean yoghurt on the immune system and sleep quality in healthy elderly subjects in Yogyakarta. The study included 17 healthy elderly aged 60-81 years. The study design was a quasi-experimental, before and after design conducted at the Abiyoso Institutional Care for elderly in Yogyakarta from April to May 2018. The subjects were given 200 ml kidney bean yoghurt everyday for 14 days. The immune system status was measured by lymphocyte count and the sleep quality was measured by the PSQI with higher scores in dicating worse sleep quality. Paired t-test was used for data analysis. Lymphocyte count after intervention (28.89±7.09) was higher than before intervention (25.96±7.41), and it was statistically significant (p=0.006). The sleep quality index after the intervention (4.88±1.83) was lower than before intervention (8.06±3.09) and the difference was statistically significant (p=0.001). This intervention study indicates that kidney bean yoghurt significantly improves both immune systems and sleeps quality among our elderly subjects.